Country risk : assessment and monitoring - Krayenbuehl, Thomas E. (Lexington, Mass. : Lexington Books, 1985)
The purpose of this book was to offer guidance to bankers, executives of multinational corporations and those concerned in government departments and international agencies on how better to assess and monitor country risk. Also the additional commercial risk involved in cross border transactions so that excessive lending or imprudent investments can be avoided.
Includes index.
Bibliography: p. 169-172.
usc 06/06/18
Loans
Keywords: Loans, Foreign; Debts, External; Country risk; International Monetary Fund; Loans, Foreign--Evaluation